Пошаговое объяснение:
1)x:19=48
48×19
x=912
2)x-261=406
406+261=667
x=667
3)c×101=404
404:101=4
c=4
4)324:y=36
324:36=9
y=9
1) [-3;4)
2) (-∞; 4)
3) [-3; +∞)
4) [-4; 6]
Пошаговое объяснение:
1) Решение первой строки:
2x+7≥1
2x≥-6
x≥-3
Решение второй строки:
x-3<1
x<4
Пересечение промежутков: x⊂[-3;4)
2) Решение первой строки:
3y<21 |:3>0, знак остаётся
y<7
Решение второй строки:
4-y>0
4>y
Пересечение промежутков: x⊂(-∞; 4)
3) Решение первой строки:
4x+9>-15
4x>-24 |:4>0, знак остаётся
x>-6
Решение второй строки:
2-x≤5
-3≤x
Пересечение промежутков: x⊂[-3; +∞)
4) Решение первой строки:
2x+3≥x-1
x≥-4
Решение второй строки:
5x-22≤x+2
4x≤24 |:4>0, знак остаётся
x≤6
Пересечение промежутков: x⊂[-4; 6]
2) y + 195 = 300 3) 920 - z = 587
y = 300 - 195 z = 920 - 587
y = 105 z = 333
5) 11y = 187 8) 324 : у = 36
y = 187 : 11 у = 324 : 36
y = 17 у = 9
Пошаговое объяснение:
если не правилно сори рада